Upstream, Downstream: Diffusion and Impacts of the Universal Product Code - Basker, Emek; Simcoe, Timothy (Journal of Political Economy, 2021)
We study the adoption, diffusion, and impacts of the Universal Product Code (UPC) between 1975 and 1992, during the initial years of the bar code system. We find evidence of network effects in the diffusion process. Matched-sample difference-in-differences estimates show that firm size and trademark registrations increase following UPC adoption by manufacturers. Industry-level import penetration also increases with domestic UPC adoption. Our findings suggest that bar codes, scanning, and related technologies helped stimulate variety-enhancing product innovation and encourage the growth of international retail supply chains.